Decoding the genome of Bacillus thuringiensis subsp. israelensis VCRC B668 to understand its mosquitocidal potential for biopesticide development - Jibi Lukose; A. Mathivanan; Bhavna Gupta; Sahadiya Mandodan; V. Abhisubesh; Kakhuangailiu Gangmei; Bhagyashree Bora; Aneha Kunnikuruvan; P. Hemaladkshmi; I. Geetha; S. Poopathi; R. Paramasivan (Brazilian Journal of Microbiology, 2026)

Snowline-driven glacier dynamics across the Indian Himalayas - Deva Jefflin A R; Chandre Gowda C; Geetha Priya M; Sushil Kumar Singh (International Journal of Remote Sensing, 2026)

Retraction notice to “Computational and experimental studies of Metallo organic framework on human epidermal cell line and anticancer potential” [Environ. Res. 201(2021) 111520] - R. Prabakarakrishnan; S. Praveen; A. Natarajan; Sabariswaran Kandasamy; K. Geetha; Ashraf Elfasakhany; Arivalagan Pugazhendhi (Environmental Research, 2026)

Retraction notice to “Persistent organic pollutants in water resources: Fate, occurrence, characterization and risk analysis” [Sci. Total Environ. 831 (2022) 154808] - J. Aravind Kumar; T. Krithiga; S. Sathish; A. Annam Renita; D. Prabu; S. Lokesh; R. Geetha; S. Karthick Raja Namasivayam; Mika Sillanpaa (Science of The Total Environment, 2026)

Diabetic foot ulcer classification using an enhanced coordinate attention integrated ConvNext model - L. Jani Anbarasi; R Neeraja; S. Geetha; R. Vidhya; Vinayakumar Ravi; D Dhanya (Physical and Engineering Sciences in Medicine, 2026)

Seismic fragility assessment of reinforced concrete bridges: a comprehensive review of methodologies, isolators, and soil structure interaction - Ashwini Satyanarayana; Dushyanth V. Babu R; H. M. Sheethal; L. Geetha (Innovative Infrastructure Solutions, 2026)

Optimizing Crop Yield Prediction and Suitability using Reinforcement Learning and Context Aware Multi-Channel Networks in IoT-Enabled Smart Agriculture - J. Jencewin; M. R. Geetha (Water Resources Management, 2026)

Personalizing treatment of pancreatitis-associated chronic pain: the need for an integrated omics approach - Cole Myers; Cheyenna M. Espinoza; Aaron Clarke; Elizabeth R. Lusczek; Feng Xie; Brian T. Steffen; Zeribe C. Nwosu; Guru Trikudanathan; Geetha Saarunya; Melena Bellin; Gregory Beilman (Inflammation Research, 2026)
Background Chronic pancreatitis (CP) is a progressive inflammatory disorder characterized by debilitating chronic pain and substantial healthcare burden. Pain mechanisms in CP are heterogeneous and incompletely integrated into clinical decision-making. This narrative review synthesizes data from human CP cohorts and complementary experimental models to summarize inflammatory, neuropathic, and metabolic drivers of pancreatitis-associated pain and to evaluate how integrated multi-omics approaches may enable mechanism-based precision management. Current treatment relies on lifestyle modification, anatomy-guided interventions, stepwise pharmacologic escalation, and surgery for refractory cases. Emerging ion-channel–targeted therapies show promise, but inconsistent patient selection and limited biomarker guidance constrain therapeutic precision. Findings CP-associated pain arises from convergent inflammatory, neuroimmune, neuropathic, and metabolic pathways that promote peripheral and central sensitization with sustained neuroplastic remodeling. Advances in clinical phenotyping have improved characterization of pain subtypes; however, integration of biologic data remains limited. Genetic association studies increasingly implicate pathways linked to severe or persistent pain phenotypes. Omics investigations have identified candidate genomic, proteomic, and metabolomic signals that may support biologically informed stratification and treatment prediction. Nevertheless, most studies are cross-sectional, modality-specific, and derived from heterogeneous cohorts with inconsistent endpoints and limited external validation. Conclusions Integration of rigorous clinical phenotyping with longitudinal, multi-omics modeling provides a framework for developing testable, mechanism-based biomarkers to guide personalized analgesic and procedural strategies while supporting opioid-sparing care. Priorities include harmonization of multicenter datasets, standardized and longitudinal pain outcome measurement, expanded paired biospecimen collection, and external validation of predictive models. Such efforts may enable biologically grounded pain stratification and facilitate translation of biomarker-guided decision tools into routine clinical practice.

sCentInDB: a database of essential oil chemical profiles of Indian medicinal plants - Shanmuga Priya Baskaran; Geetha Ranganathan; Ajaya Kumar Sahoo; Kishan Kumar; Jayalakshmi Amaresan; Kundhanathan Ramesh; R. P. Vivek-Ananth; Areejit Samal (Molecular Diversity, 2026)
Essential oils are complex mixtures of volatile compounds produced by aromatic plants and widely used in personal care, food flavoring, and pharmaceutical industry due to their odor and therapeutic properties. As a high-value and low-volume organic product, optimizing plant yield and modifying composition by leveraging knowledge on chemical profiles of essential oils can lead to enhanced bioproducts. Additionally, overharvesting of wild medicinal plants, especially in India, threatens biodiversity. Essential oil profiles of such plants can help regulate their exploitation. Here, we present sCentInDB, a manually curated FAIR-compliant DataBase of Essential oil Chemical profiles of Medicinal plants of India, compiled from published literature. sCentInDB contains data on 554 Indian medicinal plants at the plant part level, encompassing 2170 essential oil profiles, 3420 chemicals, 471 plant-part-therapeutic use associations, 120 plant-part-odor associations, and 218 plant-part-color associations. sCentInDB also compiles metadata such as sample location, isolation, and analysis methods. Subsequently, an extensive analysis of the chemical space in sCentInDB was performed. By constructing a chemical similarity network, terpenoids were found to be distributed across the network, indicating greater structural diversity. Moreover, a comparison of the scaffold diversity of chemicals in sCentInDB was performed against three other aroma libraries using cyclic system retrieval curves. Altogether, sCentInDB will serve as a valuable resource for researchers working on plant volatiles and employing genetic engineering to enhance oil yield and composition. Further, sCentInDB will aid in the establishment of quality standards for essential oils and provide vital insights for therapeutic and perfumery applications. sCentInDB is accessible at https://cb.imsc.res.in/scentindb/ . Graphical abstract Graphical abstract summarizing the workflow for constructing the sCentInDB database and analysis of the associated chemical space.

Novel bacteriophages effectively target multidrug-resistant clinical isolates of Klebsiella pneumoniae - Malavika Binitha Hari; A. L. Sreelekshmi; Pradeesh Babu; Abhijith Pulimoottil Jaykumar; Sivaraj Barath; Sharayu Magar; Sutharsan Govindarajan; John Bernet Johnson; Anil Kumar; Jayalekshmi Haripriyan; Victor Nizet; Jason Gill; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Trace-level electrochemical detection of organic pollutant metol in environmental samples using MIL-101(Cr)@F-MWCNTs nanocomposite - Bhakti Kulkarni; Thangavelu Kokulnathan; Tzyy-Jiann Wang; Mysoon M. Al-Ansari; R. Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2025)

Fusarium incarnatum Strain K23 Reprograms the Response of Tomato Seedlings to Salt Stress - N. Pallavi; Y. N. Priya Reddy; Geetha Govind; Michael Reichelt; Clabe Wekesa; C. U. Alexandra Furch; Veit Grabe; R. Uma Shaanker; Ralf Oelmüller; Karaba N. Nataraja (Journal of Plant Growth Regulation, 2025)

Aquaculture of Asian seabass (Lates calcarifer) in India: A comparative economic analysis across production systems and regions - Geetha R.; Abhinaya D.; Naffees Gowsar S. R.; Ravisankar T.; Kailasam M.; Jayakumar R.; Subburaj R.; Shinoj P.; Rajni Jain; Lal K. K.; Patil P. K. (Aquaculture International, 2025)

KERN-HIC: a hyperspectral remote sensing model for land cover classification and land use monitoring - Ganesh Babu R.; Geetha T. S.; Arul S.; Kavin Kumar K. (Environmental Monitoring and Assessment, 2025)

Europium MOFs-enabled fluorescent membranes with optimized flux, filtration, and fouling resistance for wastewater treatment: A strategy to probe MOF distribution in membranes - Gayathri Karthikeyan; Vidya Devadiga; Sakar Mohan; R. Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2025)

Correction to: Integrating solid stem and multiple disease resistance for developing climate-resilient wheat (Triticum aestivum L.) - P. Shajitha; R. Nisha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; K. Gajalakshmi; Niharikha Mallick; Prashanth Babu; Rajbir Yadav; S. Vijaishree; K. Akileshwaran; John Peter; et al. (Cereal Research Communications, 2025)

Integrating solid stem and multiple disease resistance for developing climate-resilient wheat (Triticum aestivum L.) - P. Shajitha; R. Nisha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; K. Gajalakshmi; Niharikha Mallick; Prashanth Babu; Rajbir Yadav; S. Vijaishree; K. Akileshwaran; John Peter; et al. (Cereal Research Communications, 2025)

Bimetallic transition metal dichalcogenides NixMo1-xSSe as efficient electrocatalysts for hydrogen evolution reaction in protic electrolyte - Shwetharani R; Samriti Mehta; Bhuneshwar Paswan; Itika Kainthla; Sumanth Dongre S.; Amitava Banerjee; R. Geetha Balakrishna (Fuel, 2025)

Cisgenics–An advanced breeding technique for Fruit crop amelioration - V. Boomika; M. S. Aneesa Rani; K. S. Vijai Selvaraj; P. Irene Vethamoni; R. Kalaiyarasi; P. Geetha (Euphytica, 2025)

Microscopical and histochemical assessment of Secamone emetica (Apocynaceae) Leaves -An endemic medicinal plant - Shalini. S; Sudeepthi N; Jayashre. R; Geetha DH (Flora, 2025)

Management of Diverse Weed Flora in Widely Spaced Sugarcane Plant Crop in Tropical India Through Sequential and Tank Mix Application of Herbicides - S. Anusha; P. Geetha; V. Krishnapriya; A. S. Tayade; R. Arun Kumar (Sugar Tech, 2025)

The Aegilops ventricosa derived 2NvS translocation for enhanced defense against multiple diseases in wheat - R. Nisha; P. Shajitha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; Shailendra Jha; Niharika Mallick; Rajbir Yadav; S. C. Bhardwaj; O. P. Gangwar; S. Vijaishree; M. Geetha; et al. (Journal of Crop Science and Biotechnology, 2025)

Exploring Withanolides from Withania somnifera: A Promising Avenue for Alzheimer’s Disease Treatment - Chitikela P Pullaiah; Preethi Priyadharshini SP; Phareedha SK; Yamini Nemalapalli; Geetha Birudala; S Lahari; Shanmugam Vippamakula; R Shakila; Muni Swamy Ganjayi; Raghavendra Mitta (Current Pharmacology Reports, 2025)

Effects of Metarhizium anisopliae on the histochemistry and enzymatic activities of Helicoverpa armigera (Hübner, 1809) - Yamini R; Shanmugam P.S; Murugan M; Geetha N; Meenakshi P; Srinivasan T; Premalatha K; Kandan A; Sathiyaraj G; Vivekanandhan P (Biocatalysis and Agricultural Biotechnology, 2024)

Reliability of Multi-Emissive Carbon Quantum Dots for Multiplexing; Assessing the Figures of Merit - Jomy Jose Philip; Aishwarya C.S.; Nagaraju Kottam; Chandan Hunsur Ravikumar; R Geetha Balakrishna (Journal of Fluorescence, 2024)

Preparation and characterization of activated carbon from corn cob by chemical activation and their adsorption of brilliant green dye from wastewater - Sakthivel Kumaravel; M. Geetha; Theophile Niyitanga; D. Senthil Kumar; Mysoon M. Al-Ansari; R. Mythili; Sanjeevamuthu Suganthi; L. Guganathan; A. Murugan; S. Ragupathy (Process Safety and Environmental Protection, 2024)

Manifestation of UiO-66-Zr MOF-enabled photocatalytic membranes for successive separation and degradation of dye mixtures in water remediation - K. Gayathri; K. Vinothkumar; Sakar Mohan; R. Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2024)

Quinoline-quinoline schiff-base as an effective chromogenic, fluorogenic, and smartphone assisted RGB detection of Pb2+ ion in near aqueous medium - Kathirvel R; Poongodi M; Vetriarasu V; Vivekanandan K.E; Selvakumar K; Sami Al Obaid; Arivalagan Pugazhendhi; Geetha Venkatesan (Environmental Research, 2024)

Liquid- liquid (Cyclohexanone: Cyclohexanol) separation using augmented tight nanofiltration membrane: A sustainable approach - Swathi Divakar; Nagaraj S. Naik; R. Geetha Balakrishna; Mahesh Padaki (Chemosphere, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

Recent advances in metal organic frameworks–based magnetic nanomaterials for waste water treatment - Shwetharani Ramu; Itika Kainthla; Lavanya Chandrappa; Jyothi Mannekote Shivanna; Brijesh Kumaran; R. Geetha Balakrishna (Environmental Science and Pollution Research, 2023)

In silico identification of potential inhibitors of vital monkeypox virus proteins from FDA approved drugs - Ajaya Kumar Sahoo; Priya Dharshini Augusthian; Ishwarya Muralitharan; R. P. Vivek-Ananth; Kishan Kumar; Gaurav Kumar; Geetha Ranganathan; Areejit Samal (Molecular Diversity, 2023)

Acacia furnesiana plant as a novel green source for the synthesis of NiFe2O4 magnetic nanocatalyst and as feedstock for sustainable high quality biofuel production - Veeranna R. Kattimani; K.V. Yatish; K. Pramoda; M. Sakar; R. Geetha Balakrishna (Fuel, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

A novel biomass derived activated carbon mediated AC@ZnO/NiO bifunctional nanocatalyst to produce high-quality biodiesel from dairy industry waste oil: CI engine performance and emission - Basir Maleki; Yatish Kalanakoppal Venkatesh; S. Siamak Ashraf Talesh; Hossein Esmaeili; Sakar Mohan; Geetha R. Balakrishna (Chemical Engineering Journal, 2023)

MIL-100 (Fe) integrated fibrous polyvinyl alcohol graft on cellulose acetate towards the development of green membranes; Application in multi solute rejection - Lavanya Chandra; Karthikeyarajan Vinothkumar; R Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2023)

Twisted top disease a destructive disease of sugarcane in India - R. Viswanathan; N. Geetha; K. P. Salin; R. Selvakumar; P. Malathi; A. R. Sundar; R. Nithyanantham; K. Manivannan (Indian Phytopathology, 2023)

Perovskite QD based paper microfluidic device for simultaneous detection of lung cancer biomarkers – Carcinoembryonic antigen and neuron specific enolase - Sanjayan C.G; Chandan Hunsur Ravikumar; R. Geetha Balakrishna (Chemical Engineering Journal, 2023)

Study on the workability, mechanical properties of fish tail palm fibre reinforced concrete-emphasis on fibre content and fibre length - R. Vijayalakshmi; M. Vaishnavi; R. Geetha (European Journal of Environmental and Civil Engineering, 2023)

Development of in vitro pollen germination protocol for recalcitrant triticale pollen (X Triticosecale Wittmack) - P. Jayaprakash; John Peter; P. Shajitha; V. Balaji; R. Nisha; M. Geetha; V. K. Vikas; M. Sivasamy (Cereal Research Communications, 2023)

Correction to: Adult plant stem rust resistance in durum wheat Glossy Huguenot: mapping, marker development and validation - Rohit Mago; Chunhong Chen; Xiaodi Xia; Alex Whan; Kerrie Forrest; Bhoja R. Basnet; Geetha Perera; Sutha Chandramohan; Mandeep Randhawa; Matthew Hayden; Urmil Bansal; Julio Huerta‑Espino; et al. (Theoretical and Applied Genetics, 2022)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Adult plant stem rust resistance in durum wheat Glossy Huguenot: mapping, marker development and validation - Rohit Mago; Chunhong Chen; Xiaodi Xia; Alex Whan; Kerrie Forrest; Bhoja R. Basnet; Geetha Perera; Sutha Chandramohan; Mandeep Randhawa; Matthew Hayden; Urmil Bansal; Julio Huerta-Espino; et al. (Theoretical and Applied Genetics, 2022)

Epidemiology of sugarcane wilt: predisposition by root borer Polyocha depresella a myth or reality - R. Viswanathan; R. Selvakumar; N. Geetha; C. G. Balaji; A. Annadurai; Adhini S. Pazhani; P. Malathi; A. Ramesh Sundar; R. Nithiyanantham; K. Manivannan (Indian Phytopathology, 2022)

Techno-economic evaluation of Asian seabass (Lates calcarifer) nursery rearing in small net cages (hapas) under different coastal salinities - M. Kumaran; K. P. Kumaraguru Vasagam; R. Subburaj; P. R. Anand; K. Ramachandran; R. Geetha; D. Deboral Vimala; R. Anandaraja; M. Jayanthi; C. V. Sairam (Aquaculture International, 2022)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Additive main effects and multiplicative interaction analyses of yield performance in rice genotypes for general and specific adaptation to salt stress in locations in India - S. L. Krishnamurthy; P. C. Sharma; D. K. Sharma; Y. P. Singh; V. K. Mishra; D. Burman; B. Maji; S. Mandal; S. K. Sarangi; R. K. Gautam; P. K. Singh; K. K. Manohara; et al. (Euphytica, 2021)
The aim of this study was to identify stable rice genotypes tolerant to a salt stress environment and to identify ideal mega-environments using AMMI (additive main effects and multiplicative interaction) stability model analysis. A total of 13 rice genotypes and three salt tolerance checks were evaluated across 13 salt stress locations (alkaline and saline) for the two kharif seasons of 2014 and 2015. Genotype CSR 36 (CHK3) was found to be the most ideal of those tested. Genotypes CHK2 (CST 27) and IR 87952-1-1-1-2-3-B (G05) were found to be the most stable, with above average yields. The check CSR 36 (CHK3) genotype was the best performer in the majority of the environments studied, followed by CSR 27 (CHK2) and IR 87952-1-1-1-2-3-B (G05) which were the best genotypes in the mega-environment consisting of 21 environments evaluated across stress locations and year combinations. Overall, the most promising genotype (IR 87952-1-1-1-2-3-B) had high mean yield and stability and could be used for commercial cultivation or used as donor for breeding programs across salt-affected soils. The genotypes GN13 (IR 87938-1-1-2-1-3-B) and GN11 (IR 87938-1-2-2-1-3-B) showed 60–80% yield advantage at specific salt stress locations, showing that these genotypes could be used for specific environments of salt-affected soils in India.

Identification of rice genotypes for seedling stage multiple abiotic stress tolerance - Tinu Thomas; J. Purushothaman; R. Janarthanan; N. Anusuya; Prasanna Geetha Medisetti; J. Karthick; S. Nadaradjan; S. Thirumeni (Plant Physiology Reports, 2020)

Trends, causes, and indices of import rejections in international shrimp trade with special reference to India: a 15-year longitudinal analysis - R. Geetha; T. Ravisankar; P. K. Patil; Satheesha Avunje; S. Vinoth; C. V. Sairam; K. K. Vijayan (Aquaculture International, 2020)

Recursive partitioning algorithm in water quality prediction - M. Geetha Jenifel; R. Jemila Rose (International Journal of Environmental Science and Technology, 2020)

Characterization of inertia gravity waves and associated dynamics in the lower stratosphere over the Indian Antarctic station, Bharati (69.4°S, 76.2°E) during austral summers - N. Koushik; Karanam Kishore Kumar; K. V. Subrahmanyam; Geetha Ramkumar; I. A. Girach; M. Santosh; K. Nalini; M. Nazeer; P. R. Shreedevi (Climate Dynamics, 2019)

Bio-intensive Modulation of Sugarcane Ratoon Rhizosphere for Enhanced Soil Health and Sugarcane Productivity Under Tropical Indian Condition - A. S. Tayade; P. Geetha; S. Anusha; R. Dhanapal; K. Hari (Sugar Tech, 2019)

Efficient Water Management in Sugarcane with Composted Coir Pith and Sugarcane Trash Under Tropical Indian Conditions - R. Dhanapal; A. S. Tayade; A. Bhaskaran; P. Geetha (Sugar Tech, 2019)

Evaluation of genetic stability using FRAPD markers as novel method along with antioxidant and anti-diabetic properties of micropropagated Salacia chinensis L. - Majid Bagnazari; M. G. Mahesh; Mehdi Saidi; K. R. Kini; H. S. Prakash; N. Geetha (Acta Physiologiae Plantarum, 2018)

New camphor hybrids: lipophilic enhancement improves antimicrobial efficacy against drug-resistant pathogenic microbes and intestinal worms - Ramalingam Peraman; Amit K. Tiwari; M. Geetha Vani; J. Hemanth; Y. Geetha Sree; K. Karthik; Charles R. Ashby; Y. Padmanabha Reddy; Raghuveer V. Pemmidi (Medicinal Chemistry Research, 2018)

Climate change projections for Tamil Nadu, India: deriving high-resolution climate data by a downscaling approach using PRECIS - Prasanta Kumar Bal; A. Ramachandran; R. Geetha; B. Bhaskaran; P. Thirumurugan; J. Indumathi; N. Jayanthi (Theoretical and Applied Climatology, 2016)

Genetic clustering of recent classical swine fever virus isolates from Karnataka, India revealed the emergence of subtype 2.2 replacing subtype 1.1 - D. B. Shivaraj; S. S. Patil; D. Rathnamma; D. Hemadri; S. Isloor; S. Geetha; G. B. Manjunathareddy; M. R. Gajendragad; H. Rahman (VirusDisease, 2015)

Longitudinal variations of coral reef features in the Marine National Park, Gulf of Kachchh - J. S. Yogesh Kumar; N. Marimuthu; S. Geetha; Ch. Satyanarayana; K. Venkataraman; R. D. Kamboj (Journal of Coastal Conservation, 2014)

Coregulation of host–response genes in integument: switchover of gene expression correlation pattern and impaired immune responses induced by dipteran parasite infection in the silkworm, Bombyx mori - Anitha Jayaram; Appukuttan Nair R. Pradeep; Arvind K. Awasthi; Geetha N. Murthy; Kangayam M. Ponnuvel; Sirigineedi Sasibhushan; Guruprasad C. Rao (Journal of Applied Genetics, 2014)

A Fluorescent Chemodosimeter for Hg2+Based on a Spirolactam Ring-Opening Strategy and its Application Towards Mercury Determination in Aqueous and Cellular Media - Kempahanumakkagaari Suresh Kumar; Thippeswamy Ramakrishnappa; R. Geetha Balakrishna; Mallingappagari Pandurangappa (Journal of Fluorescence, 2014)

Growth response of Casuarina equisetifolia Forst. rooted stem cuttings to Frankia in nursery and field conditions - A Karthikeyan; K Chandrasekaran; M Geetha; R Kalaiselvi (Journal of Biosciences, 2013)

Characterization of mode of reproduction in Commiphora wightii [(Arnot) Bhandari] reveals novel pollen–pistil interaction and occurrence of obligate sexual female plants - K. A. Geetha; Aarti Kawane; Ashok Kumar Bishoyi; Arunkumar Phurailatpam; C. Ankita; S. K. Malik; R. Srinivasan; S. R. Bhat (Trees, 2013)

Bacillus thuringiensis Isolates from Great Nicobar Islands - R. Asokan; H. M. Mahadeva Swamy; Ajanta Birah; Geetha G. Thimmegowda (Current Microbiology, 2013)

Activation of autophagic programmed cell death and innate immune gene expression reveals immuno-competence of integumental epithelium in Bombyx mori infected by a dipteran parasitoid - Appukuttan Nair R. Pradeep; Jayaram Anitha; Arvind K. Awasthi; Mohd. A. Babu; Murthy N. Geetha; Hariharan K. Arun; Sagar Chandrashekhar; Guruprasad C. Rao; Nanjappa B. Vijayaprakash (Cell and Tissue Research, 2013)

Regional Scale Erosion Assessment of a Sub-tropical Highland Segment in the Western Ghats of Kerala, South India - V. Prasannakumar; H. Vijith; N. Geetha; R. Shiny (Water Resources Management, 2011)

SCS-CN-based Continuous Simulation Model for Hydrologic Forecasting - K. Geetha; S. K. Mishra; T. I. Eldho; A. K. Rastogi; R. P. Pandey (Water Resources Management, 2008)

Effects of presowing treatments, desiccation and storage conditions on germination of Strychnos nux-vomica seeds, a valuable medicinal plant - V. Sivakumar; R. Anandalakshmi; R. R. Warrier; M. Tigabu; P. C. Odén; S. N. Vijayachandran; S. Geetha; B. G. Singh (New Forests, 2006)

Immunomodulatory effects of seabuckthorn (Hippophae rhamnoides L.) against chromium (VI) induced immunosuppression - S. Geetha; Vandana Singh; M. Sai Ram; G. Ilavazhagan; P. K. Banerjee; R. C. Sawhney (Molecular and Cellular Biochemistry, 2005)

Faecal fat content in healthy adults by the ‘acid steatocrit method’ - Anita R. Bijoor; S. Geetha; T. Venkatesh (Indian Journal of Clinical Biochemistry, 2004)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Safety profile of ibuprofen suspension in young children - E. Ashraf; L. Ford; R. Geetha; S. Cooper (Inflammopharmacology, 1999)

Antifungal Activity of Some B,D-Seco Limonoids from Two Meliaceous Plants - T. R. Govindachari; G. Suresh; B. Banumathy; S. Masilamani; Geetha Gopalakrishnan; G. N. Krishna Kumari (Journal of Chemical Ecology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Identification of antifungal compounds from the seed oil ofAzadirachta Indica - T. R. Govindachari; G. Suresh; Geetha Gopalakrishnan; Balaganesan Banumathy; S. Masilamani (Phytoparasitica, 1998)